Cultivating Effective Speaking Skills in Primary Education (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This comprehensive article explores the importance of developing speaking skills in primary education and provides practical strategies for educators to enhance students' oral communication abilities. Emphasizing the crucial role of effective speaking in academic success and social interaction, the article advocates for creating a supportive classroom environment where students feel empowered to express themselves confidently. By offering actionable strategies such as encouraging oral communication, modeling effective speaking habits, scaffolding speaking activities, providing constructive feedback, and integrating speaking across the curriculum, educators can cultivate students' speaking proficiency from an early age. With a focus on fostering both individual expression and collaborative interaction, this article serves as a valuable resource for educators seeking to promote the holistic development of primary school students through effective speaking instruction.